2018
DOI: 10.1259/bjr.20170654
|View full text |Cite
|
Sign up to set email alerts
|

Target volume motion during anal cancer image guided radiotherapy using cone-beam computed tomography

Abstract: The AC is susceptible to volume changes and shape deformations. Care must be taken when calculating or considering reducing the PTV margin to the anus. Advances in knowledge: Within a limited field of research, this study provides further knowledge of how the AC deforms during anal cancer radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There is very limited published data on IGRT in anal cancer. Two studies have examined setup errors for bony anatomy during tomotherapy and IMRT; they found systematic and random translational errors of 1-3mm and 3-4mm, respectively [100,101]. Brooks et al also studied primary tumour motion during IMRT, and found significant inter-fraction movement relatively to bony anatomy (>10 mm) [101].…”
Section: Anal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…There is very limited published data on IGRT in anal cancer. Two studies have examined setup errors for bony anatomy during tomotherapy and IMRT; they found systematic and random translational errors of 1-3mm and 3-4mm, respectively [100,101]. Brooks et al also studied primary tumour motion during IMRT, and found significant inter-fraction movement relatively to bony anatomy (>10 mm) [101].…”
Section: Anal Cancermentioning
confidence: 99%
“…Two studies have examined setup errors for bony anatomy during tomotherapy and IMRT; they found systematic and random translational errors of 1-3mm and 3-4mm, respectively [100,101]. Brooks et al also studied primary tumour motion during IMRT, and found significant inter-fraction movement relatively to bony anatomy (>10 mm) [101]. The main cause of primary tumour movement appears to be a combination of bowel gas & filling variation (high tumours) and buttock displacement (low tumours).…”
Section: Anal Cancermentioning
confidence: 99%